Collimated proton pencil-beam scanning for superficial targets: impact of the order of range shifter and aperture. (20th April 2018) - Bäumer, C; Janson, M; Timmermann, B; Wulff, J
Abstract: To assess if apertures shall be mounted upstream or downstream of a range shifting block if these field-shaping devices are combined with the pencil-beam scanning delivery technique (PBS). The lateral dose fall-off served as a benchmark parameter. Both options realizing PBS-with-apertures were compared to the uniform scanning mode. We also evaluated the difference regarding the out-of-field dose caused by interactions of protons in beam-shaping devices. The potential benefit of the downstream configuration over the upstream configuration was estimated analytically. Guided by this theoretical evaluation a mechanical adapter was developed which transforms the upstream configuration provided by the proton machine vendor to a downstream configuration. Transversal dose profiles were calculated with the Monte-Carlo based dose engine of the commercial treatment planning system RayStation 6. Two-dimensional dose planes were measured with an ionization chamber array and a scintillation detector at different depths and compared to the calculation. Additionally, a clinical example for the irradiation of the orbit was compared for both PBS options and a uniform scanning treatment plan. Assuming the same air gap the lateral dose fall-off at the field edge at a few centimeter depth is 20% smaller for the aperture-downstream configuration than for the upstream one. For both options of PBS-with-apertures the dose fall-off is larger than in uniform scanning delivery mode if the minimum accelerator energy is 100 MeV. The RayStation treatment planning system calculated the width of the lateral dose fall-off with an accuracy of typically 0.1 mm–0.3 mm. Although experiments and calculations indicate a ranking of the three delivery options regarding lateral dose fall-off, there seems to be a limited impact on a multi-field treatment plan.